If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3v + -36 = -42 Reorder the terms: -36 + 3v = -42 Solving -36 + 3v = -42 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 3v = -42 + 36 Combine like terms: -36 + 36 = 0 0 + 3v = -42 + 36 3v = -42 + 36 Combine like terms: -42 + 36 = -6 3v = -6 Divide each side by '3'. v = -2 Simplifying v = -2
| 10x+5=12y+5 | | 15y+20= | | 4r+(-12)=48 | | 15y/4=90 | | 2x-6+4x+28=6x+22 | | 3(x+1)x+4(x+3)=22 | | 4(2x-y)=2y+5 | | 147.1875=3r(3.14r^2) | | 0.4(x+25)-3=0.2(7x+10) | | 13x-4x=-63 | | 3y+4z=9fory | | 8x=6y+5 | | 22-6y+y^2-14=0 | | 83=15+2(x) | | -8a=-8b | | (3)(2x-4)+2(2x-4)-x=-17 | | 12=15*Z-1/5 | | x+(-40)=y | | X^2+4x-62.5=0 | | 15=5+9(3) | | b+-4=-4 | | -5x=-5y | | g/3-0.9=-.4 | | 85=17p | | 7x^4z^3/28y^3 | | (6x+2)(3x+4)=64 | | 5y(y+2)= | | -36x-36=0 | | 3(2x+4)-2x=3(2-4x) | | 5[m+4]=-2[-4-m]+3 | | (5-5):(1/5) | | 2*3+5=360 |